PENERAPAN DISIPLIN KERJA PEGAWAI MELALUI ABSENSI FINGER PRINT DI SDN 25 MANADO - NURIANTO, ANGGELIKA; ROMPAS, WELSON YAPPI; KIYAI, BURHANUDDIN (JURNAL ADMINISTRASI PUBLIK, 2020)
AbstractIn order to discipline employees, up to SDN 25 Manado has implemented finger print attendance becauseall this time on manual absences (only in the form of attendance books), employees are still found to beabsent, coming and going home from school not according to the specified hours and staff and teacherswhose performance is as the maximum number of teachers does not match what is received in this caseEmployee Perfomance Allowance money (TKD). This research formulation is how the application ofemployee work discipline through finger print attendance in SDN 25 Manado? The purpose of this studywas to describe the application of employee work discipline through finger print attendance at SDN 25Manado. In this tudy the research method used was qualitative with the type of descriptive approach,datacollection techniques used were interviews, observation, documentation. The research results pbtainedwere, schools that had previously used fnger print attendance but there were still employees anda teacherswho could manipulate attendance data because the data was still managed entirely by the scholl. Fingerprint attendance is now able to discipline employees because of the absenteeism data recorded directly intothe Manado City Civil Service Agency.Keywords: Application Of Dicipline, Finger Print Attendance.